(untitled) (Indian Journal of Nematology, 2019)
Among the thirteen native isolates of Trichoderma harzianum of Indian Type Culture Collection (ITCC) screened against the plant-parasitic nematode, Meloidogyne incognita, using the cell free extracts (CFF), the average antibiosis effect was the highest in ITCC 6888 leading to 97.30% mortality in infective juveniles (J2) .The egg masses incubated in the CFF for 20 days caused 99.50% egg hatch inhibition, compared to control. The attachment of spores and mycelia increased with an increase in days of incubation. The isolate was found to produce 51.42 U/mL of chitinase and 4.27U/mL of protease. On comparing the thirteen isolates of the fungal species, it was found that a level greater than 29U/mL resulted in egg parasitization, irrespective of protease levels.